An evaluation of the Master of Arts (MA) in education, major in Guidance and Counseling program of De La Salle University - Tengco, Lydia Libreja (Animo Repository, 1989)
Based on the evaluation model proposed by Astin and Panos, the Master of Arts in Education major in Guidance and Counseling Program of De La Salle University was assessed based on the following components:Program InputEducational qualifications and work experiences of respondents prior to MA studies.Program OperationDegree/level of satisfaction and relevance of the various phases of the program such as objectives, courses offered, reasons for or not pursuing MA studies, strong and weak points of the program.Program OutputRespondents' profile re: Work experiences, competence in implementing the skills learned, level of satisfaction as regards usefulness and relevance of subject matter offerings to current jobs.The descriptive method of research and questionnaire technique were used in this study. Data were gathered from three groups of respondents-31 graduates of the program, 27 who completed their academic requirements and 13 dropouts. The data were transmitted in simple statistics, analyzed and interpreted in the light of the questions raised.Majority of the respondents were in different disciplines other than Psychology and Guidance, and varied work experiences such as guidance, administration/management, teaching, among others.The various program components were rated satisfactory with similarities and differences (among and between groups) in their assessment of certain indicators (e.g. personality characteristics of faculty, class scheduling, screening measures, mentors' availability and guidance extended in the preparation of thesis proposals. The strong point of the program was its person-oriented aspect in guidance and counseling-a take off in human relations training and religious education. The weak point was the inadequacy of assistance in the preparation of thesis proposals.Four of the respondents dropped their studies due to dissatisfaction (favorite mentors were not available) and time and financial constraints.After having completed or left MA studies, the respondents became directors, coordinators and department heads in Guidance and Counseling areas. Others became managers, program assistants and teachers. Sixteen had two or more jobs in Guidance and Counseling and five in Administration/Management. They also revealed that the basic, major and elective courses offered were useful in current jobs. The skills gained were very important in organizing, coordinating and evaluation guidance and counseling programs, testing, research, referrals and job placements.The study concluded that:1. The respondents (despite differences in educational qualification and work experiences) were generally satisfied with the program operation and program output of DLSU's MA Program major in Guidance and Counseling.2. The respondents continued to be involved in guidance activities such as pursuing guidance jobs or by being members of guidance organizations.3. They believed in the usefulness, relevance and extent of what they learned and the skills gained in the jobs.